Mass Optimization of Rocket Nozzles Using Ablative Materials: A Case Study on Indonesian Sounding Rockets - Abrizal, Haryadi; Juwono, Ariadne Laksmidevi; Jihad, Bagus Hayatul (BRIN Publishing, 2025)
This study presents a comprehensive redesign of the RX450 sounding rocket nozzleaimed at reducing mass while maintaining thermal and structural integrity. The baselinedesign, characterized by heavy steel casing and monolithic graphite liners, imposes significantlimitations on payload capacity and flight performance due to its weight and thermalmanagement challenges. The proposed design replaces the divergent section’s steel casingwith a combination of ablative silica-phenolic composite liners and aluminum 6061 structuralsupport, achieving a substantial mass reduction from approximately 59 kg to 14.5 kgin this critical region. Thermal simulations demonstrate that the addition of a glass-phenolicinsulation layer effectively limits heat transfer to the metallic casing, allowing for thinnerstructural components without compromising safety. Structural analyses confirm thatboth steel and aluminum sections maintain high safety factors under operational loads.Comparative evaluations of alternative configurations further highlight the benefits of advancedcomposite materials and innovative structural concepts, with the lightest modelreducing total nozzle mass by around 40% compared to the baseline. While these resultsare based on literature-derived properties and simplified assumptions, they underscore thepotential of integrating ablative composites and lightweight metals to enhance rocket nozzleperformance. Future work will focus on detailed thermochemical modeling, experimentalvalidation, and full-scale testing to confirm thermal-structural behavior and erosionrates. Overall, this study supports Indonesia’s strategic objective of advancing indigenousrocket technology through accessible, high-performance materials and design innovations.